An In-Depth Analysis of the Students’ Perceptions of How the Final Exam Administered in Package C Program - Kartika Waty, Evy Ratna; Nengsih, Yanti Karmila; Handrianto, Ciptro; Rasool, Shahid (Journal of Nonformal Education, 2024)
Assessments are essential in influencing students’ academic results, but there are still worries about the equity and thoroughness of tests created by tutors for different subjects. This research examines how students view these assessments in Citizenship Education, Islamic Religious Education, and History Education. The main goal is to investigate how Package C Program students view the distribution and quality of final exam questions and evaluate their preparedness and performance. This qualitative study used thematic analysis on interviews with 20 randomly chosen Package C Program students in Palembang. The information was examined to find common themes on how feel about their readiness and the tutors’ involvement in creating exams. The results suggest that students believe the exam questions do not accurately represent their understanding or what they have learned. Numerous individuals are unhappy with mistakes in the test questions, which hinder their success. The study also identifies differences between students’ anticipations and the real exam material. Prejudiced evaluation methods and varying test creation by educators can greatly harm student learning and the development of future educational policies. Improvements are necessary in exam design to guarantee fairness and accuracy. This research offers fresh perspectives on how the quality of exams affects student performance and highlights the necessity of inclusive test development with input from various parties to prevent biases.